Future Long-Baseline Neutrino Facilities and Detectors - Milind Diwan; Rob Edgecock; Takuya Hasegawa; Thomas Patzak; Masato Shiozawa; Jim Strait (Advances in High Energy Physics)
We review the ongoing effort in the US, Japan, and Europe of the scientific community to study the location and the detector performance of the next-generation long-baseline neutrino facility. For many decades, research on the properties of neutrinos and the use of neutrinos to study the fundamental building blocks of matter has unveiled new, unexpected laws of nature. Results of neutrino experiments have triggered a tremendous amount of development in theory: theories beyond the standard model or at least extensions of it and development of the standard solar model and modeling of supernova explosions as well as the development of theories to explain the matter-antimatter asymmetry in the universe. Neutrino physics is one of the most dynamic and exciting fields of research in fundamental particle physics and astrophysics. The next-generation neutrino detector will address two aspects: fundamental properties of the neutrino like mass hierarchy, mixing angles, and the CP phase, and low-energy neutrino astronomy with solar, atmospheric, and supernova neutrinos. Such a new detector naturally allows for major improvements in the search for nucleon decay. A next-generation neutrino observatory needs a huge, megaton scale detector which in turn has to be installed in a new, international underground laboratory, capable of hosting such a huge detector.